Implementasi Technology Leadership dalam Upaya Peningkatan Digital Literacy dan Budaya Mutu di SDN Sungai Miai 11 Banjarmasin - Zain, Rd. Achmad Surya Mi'raj; Fadilah, Syarif; Ramadhan, Surya (Jurnal Likhitaprajna, 2025)
The transformation of education in the digital era demands fundamental changes in the educational approach, where schools must adapt to the needs of students who live in a digital ecosystem. This study aims to analyze the implementation of leadership (technology leadership) in improving teachers' digital literacy and building a culture of quality, especially in the aspects of interpersonal and communication skills, staff development and training, and evaluation and research. Using a descriptive qualitative approach, the study was conducted at SDN Sungai Miai 11 Banjarmasin with research subjects including the principal, two class teachers, two subject teachers, and one administrative staff. Data collection was carried out through in-depth interviews, participatory observations, and document studies. The results of the study show that the technology leadership strategy implemented has succeeded in encouraging an increase in teachers' digital competence through continuous training and a technology-based evaluation system, as well as increasing the efficiency of school management, even though it still faces infrastructure challenges and disparities in digital competence among teachers. These findings emphasize the importance of adaptive leadership in supporting digital transformation in the educational environment.